Stemming cardiovascular diseases in Qatar - Nature Research (16552612) (2015)
A new study by researchers at the Weill Cornell Medical College in New York and in Doha, Qatar, suggests that public health strategies could have a major impact on the incidence of cardiovascular diseases in the Qatari population. Paul Christos and his colleagues examined demographic, lifestyle and medical information of 512 heart attack and 262 stroke patients admitted to the Hamad Medical Corporation between June 2006 and June 2008, and compared them to that of 382 control patients randomly selected from unrelated departments of the hospital during the same period. They found that more than two-thirds of heart attacks and one half of strokes occurred in people under 55 years of age, with 12% and 7%, respectively, in people under 40 — which is among the highest rates in young people around the world. Most of these were male, with Qatari nationals making up 13% of heart attack and 25% of the cases of stroke. Expatriates, who make up more than 70% of the population of the small Gulf state, made up the rest. About 40% of the study participants were overweight and an additional 30% were obese. Many of the heart attack and stroke patients had diabetes, hypertension, high cholesterol, and/or were smokers, whereas controls were much less likely to have these factors. All of these factors are associated with reduced physical activity and increased consumption of high-fat foods. “Both Qatari nationals and expatriates should adopt healthier lifestyles to reduce the prevalence of these risk factors,” says Christos. Diabetes was the largest preventable risk factor to decrease heart attacks and strokes. Heart attack and stroke are the leading causes of death and disability worldwide, which have killed an estimated 17.1 million people in 2004, according to the World Health Organization. This is projected to increase to more than 23 million by 2030, with the largest increase to occur throughout the Middle East, due in part to the adoption of the sedentary Western lifestyle. The findings show that the risk factors in Qatar are comparable with those reported in 52 other countries around the world. The importance of diabetes as a risk factor, however, was found to be higher than other countries in the Gulf region and significantly higher than the US. “Public health officials should design programmes to improve the prevention, diagnosis, and management of risk factors such as diabetes and hypertension,” says Christos, as well as work on effective awareness campaigns to create a culture of preventive health in Qatar. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0